Associations between vitamin K and systemic immune and inflammation biomarkers: a population-based study from the NHANES (2007–2020) - Luo, Wenjiao; Ye, Dong; Zhao, Kun; Zhou, Liang; Wu, Yanfei; Ge, Qiuhua (Frontiers in Nutrition, 2025)
BackgroundWith the aging of the population, finding effective interventions and treatments to delay chronic inflammation-related diseases is an urgent problem to be solved. Previous studies on animals have proposed that vitamin K can inhibit inflammation and may be a potential regulator of the immune inflammatory response. These findings suggested that increasing intake of vitamin K might also help reduce inflammation.MethodsThis study included 36,895 people from the National Health and Nutrition Examination Survey (2007–2020). Multivariate linear regression and restricted cubic spline analyses were conducted to explore the association between vitamin K intake and various immune inflammatory factors. Subgroup analyses were performed based on age, gender, ethnicity, BMI, hyperlipidemia, diabetes and hypertension.ResultsAfter multivariable adjustment, vitamin K intake is negatively correlated with SII, SIRI, SIIRI, NLR, white blood cell, neutrophil, and monocyte. When the level of vitamin K intake was less than 237.7 mcg/d, RAR showed a significant decreasing trend with the increase of vitamin K. When the vitamin K intake level was lower than 75.1 mcg/d, the basophil showed a downward trend with the increase of intake. However, when vitamin K levels exceed the inflection point, the above association no longer exists.ConclusionThese findings reveal that vitamin K intake is associated with reduced inflammatory status and improvements in immune inflammatory biomarkers. Vitamin K may modulate systemic immune and inflammatory markers, which may play a role in the development of chronic inflammation.